Analysis of Modernization Movements in Housing During the Early Republican Period: Karabük, Türkiye - Ayşe Merve Saraçoğlu Gezer; Ayşen Esra Bölükbaşı Ertürk (Buildings)
As a unit, housing is one of the most important elements affected by social, economic, and cultural changes in every period of human history. In all ages, from ancient times to the present, housing has not only met the need for shelter, but also reflected people’s lifestyles and values and the technological developments of the period. Housing architecture emerges as a type of structure that has been continuously evolving in every period and is affected by the changes experienced by societies. In this study, the idea that houses are not only structural products, but the structures that have become homes for humans, is approached and discussed through concepts such as spatial organization, relationality, accessibility, visibility, density of use, depth, privacy, and belonging. The Yenişehir district in Karabük province, which is thought to have been transformed into design by considering these concepts, also constitutes the focus area of the study idea in this sense. The houses located in the Yenişehir district, which was selected because it contains concrete examples of the modernization efforts of the Early Republican Period of Türkiye and is an example of industrial housing production, have been numerically evaluated within the scope of this study with the data obtained from the space syntax analysis and the depthMapX program (v0.8.0). In this way, it raises the question of whether it is possible to create housing settlements for people in the transition from agricultural society to industrial society without disrupting the socio-cultural structure of society. As a result, it has been seen that the houses in Yenişehir are designed functionally and human-oriented, and they also consider the dynamics of society.